Antioxidant and Antidiabetic Activities of Flavonoid Derivative Compounds Isolated from Sclerocarya birrea Leaves - L. Ndwandwe, Sithembiso; T. Olivier, Mutendela; S. Gololo, Sechene (Asian Journal of Chemistry, 2020)
Sclerocarya birrea is one of many medicinal plants used in African traditional medicine for treatment of diabetes. Bioassay-guided fractionation of the ethanolic crude extract of the leaves of the plant species led to the isolation of a pure compound (CMP-1). The pure compound showed antioxidant and antidiabetic activities with average IC50 values of 1.04 mg/mL and 46 μg/mL, respectively that were well comparable to the crude extract and known standards compounds, ascorbic acid and quercetin. The spectroscopic profiling of the purified compound revealed a flavonoid derivative structural skeleton. The findings of the study suggested that the flavonoid derivative compounds play a major role towards the medicinal value of Sclerocarya birrea.